Tilt, twist, and coiling in beta-barrel membrane proteins: relation to infrared dichroism. - Páli, T (2001)
The x-ray coordinates of beta-barrel transmembrane proteins from the porins superfamily and relatives are used to calculate the mean tilt of the beta-strands and their mean local twist and coiling angles. The 13 proteins examined correspond to beta-barrels with 8 to 22 strands, and shear numbers ranging from 8 to 24. The results are compared with predictions from the model of Murzin, Lesk, and Chothia for symmetrical regular barrels. Good agreement is found for the mean strand tilt, but the twist angles are smaller than those for open beta-sheets and beta-barrels with shorter strands. The model is reparameterised to account for the reduced twist characteristic of long-stranded transmembrane beta-barrels. This produces predictions of both twist and coiling angles that are in agreement with the mean values obtained from the x-ray structures. With the optimized parameters, the model can then be used to determine twist and coiling angles of transmembrane beta-barrels from measurements of the amide band infrared dichroism in oriented membranes. Satisfactory agreement is obtained for OmpF. The strand tilt obtained from the x-ray coordinates, or from the reparameterised model, can be combined with infrared dichroism measurements to obtain information on the orientation of the beta-barrel assembly in the membrane.